Efficacy of alternate day versus daily atorvastatin in reduction of low density lipoprotein cholesterol: a prospective, randomized, open labelled, parallel group study - Mankar, Nishikant Nandlal; Zad, Vijay Ramkrishna; Vakharia, Monali Pradeep (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cardiovascular disease (CVD) is the leading cause of death in India and worldwide. Hypercholesterolemia plays a pivotal role in atherogenesis which gave rise to universally accepted cholesterol diet-CVD hypothesis. Statins are the most potent and commonly used drugs for treating hypercholesterolemia. With atorvastatin, because of the long lasting active metabolites, half-life of HMG-CoA reductase inhibition reaches 20 to 30 hours. Thus, it is conceivable that alternate-day atorvastatin treatment might be effective in maintaining the lipid-lowering efficacy. Methods: In this prospective, randomized, open labelled, parallel group study, 100 participants with serum low density cholesterol (LDL-C) level 100 mg/dL-190 mg/dL were recruited. Group A received 20 mg atorvastatin on alternate day and group B received 20 mg atorvastatin daily for 12 weeks. Follow up visits were scheduled at 6 and 12 weeks at which fasting serum LDL-C, serum TC, serum TG, serum HDL were estimated. Creatinine phosphokinase (CPK), aspartate transaminase (AST) and alanine transaminase (ALT) estimations were also done and participants were examined for occurrence of myalgia, jaundice or any other adverse effect. Results: A statistically significant reduction in LDL-C, TC, and TG was seen in both the groups when compared to baseline. At 12 weeks, the LDL-C reduction in alternate day atorvastatin group was 34.63% whereas in daily atorvastatin group, it was 38.75.The reduction in levels of TC in alternate day and daily atorvastatin group was 24.64% and 25.85% respectively. Both the regimens were well tolerated. Conclusions: The alternate-day dosing of atorvastatin is as efficacious and safe as that of its daily dosing.